2002
DOI: 10.1002/ana.10160
|View full text |Cite
|
Sign up to set email alerts
|

Cell death in experimental intracerebral hemorrhage: The “black hole” model of hemorrhagic damage

Abstract: Intracerebral hemorrhage (ICH) has a poor prognosis that may be the consequence of the hematoma's effect on adjacent and remote brain regions. Little is known about the mechanism, location, and severity of such effects. In this study, rats subjected to intracerebral blood injection were examined at 100 days. Stereology (neuronal count and density) and volume measures in the perihematoma rim, the adjacent and overlying brain, and the substantia nigra pars reticulata (SNr) were compared with contralateral brain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
117
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(124 citation statements)
references
References 23 publications
5
117
0
1
Order By: Relevance
“…Thus, while it is possible that atrophied neurons did recover, they may also have died off thereby giving the impression of recovery. Arguing against this are collagenase studies that show only a few neurons dying beyond 7 days post-ICH (Felberg et al, 2002;Xue and Del Bigio, 2003). This finding, however, may depend upon initial insult severity, which appears in those studies to be less than that presently used.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, while it is possible that atrophied neurons did recover, they may also have died off thereby giving the impression of recovery. Arguing against this are collagenase studies that show only a few neurons dying beyond 7 days post-ICH (Felberg et al, 2002;Xue and Del Bigio, 2003). This finding, however, may depend upon initial insult severity, which appears in those studies to be less than that presently used.…”
Section: Discussionmentioning
confidence: 95%
“…Collagenase intracerebral hemorrhage causes significantly greater loss of cortical projections, particularly in the projections from the somatosensory and motor cortical areas contralateral to the striatum, which are nearly completely lost after cICH. In rat cICH, there is loss of connections to the striatum with a modest reduction in neurons that project from the substantia nigra to the striatum, 31 a decrease in cortical projections from the ipsilateral motor cortex 32 and thinning of ipsilateral cortex. 26 There are no reports of axonal loss in the rat in bICH.…”
Section: Discussionmentioning
confidence: 98%
“…This is followed by delayed neuronal injury in the peri-hematoma region (Del Bigio et al, 1996;Felberg et al, 2002), which is sometimes quite limited. Several studies have shown cell loss in distal, interconnected regions such as the substantia nigra (Felberg et al, 2002;MacLellan et al, 2008). It is clear that progressive atrophy occurs after ICH (Nguyen et al, 2008b).…”
Section: Outcome End Pointsmentioning
confidence: 99%